P‐Menthadienes as Biorenewable Feedstocks for a Monoterpene‐Based Biorefinery. (26th March 2021) - Tibbetts, Joshua D.; Bull, Steven D.
Abstract: A terpene‐based biorefinery is described that uses crude sulfate turpentine (CST) and gum turpentine (GT) to produce mixtures of p ‐menthadienes ( p ‐MeDs) as biorenewable terpene feedstocks. An acid catalyzed ring opening reaction (6 m aq. H2 SO4, 90 °C) is first used to convert the major bicyclic monoterpenes (α‐pinene, β‐pinene, and 3‐carene) in untreated CST (or GT with 5 mol% Me2 S) into mixtures of monocyclic p ‐MeDs. These unpurified sulfurous p ‐MeD mixtures (α‐terpinene, γ‐terpinene, and isoterpinolene) are then used as feedstocks for oxidative aromatization (OA), ozonolysis, Diels–Alder, and hydrogenation reactions to produce p ‐cymene, fragrances, anti‐oxidants, drugs, biopolymers, and biofuels. Mechanistic studies of the OA reaction used to convert the p ‐MeDs into p ‐cymene reveal that p ‐cymene hydroperoxide acts as an initiator to produce polar radical intermediates that are stabilized by DMSO generated in situ through aerobic oxidation of Me2 S. This enables CST and GT to be converted into biorenewable p ‐cymene in 50–60% yields (two steps) using a process that only requires aqueous acid, oxygen, heat, and a final distillation step. Abstract : A terpene‐based biorefinery model is developed that is built around utilization of industrial waste streams (crude sulfate turpentine), with a view to transitioning toward a biobased chemical economy. Development of a sustainable route to a core intermediate, p ‐cymene, allows a range of valuable fragrances, biofuels, solvents, commodity chemicals, and polymers to be produced from biorenewable, turpentine‐derived p ‐menthadienes.